2016
DOI: 10.1002/hup.2524
|View full text |Cite
|
Sign up to set email alerts
|

A simulated car‐driving study on the effects of acute administration of levocetirizine, fexofenadine, and diphenhydramine in healthy Japanese volunteers

Abstract: Levocetirizine and fexofenadine did not impair psychomotor performance in subjects performing simulated car-driving tasks, while diphenhydramine did impair psychomotor performance in the subjects. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Finally, 51 RCTs satisfied the inclusion criteria and then were included in our meta-analysis [959]. Notably, partial data from 8 RCTs [15, 24, 28, 30, 36, 53, 56, 58] were only reported in graphics and; the attempt to obtain data directly from the authors failed, so graphics were digitized and the SD were estimated using an imputation method.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, 51 RCTs satisfied the inclusion criteria and then were included in our meta-analysis [959]. Notably, partial data from 8 RCTs [15, 24, 28, 30, 36, 53, 56, 58] were only reported in graphics and; the attempt to obtain data directly from the authors failed, so graphics were digitized and the SD were estimated using an imputation method.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Forty-one studies reported AE after taking fexofenadine [9–11, 1326, 2830, 3236, 3954]. Of 41 studies, 10 compared with the first-generation antihistamines [15, 19, 24, 2830, 43, 49, 50, 53], 22 compared with the second-generation antihistamines [9, 14, 1618, 2023, 25, 28, 33, 35, 36, 40, 44, 4749, 5254], and 37 compared with placebo [9–11, 1317, 1925, 2830, 3234, 36, 3949, 5154]. When compared with the first-generation antihistamines, as demonstrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In many day-to-day situations consistently fast reaction times are important, such as in driving a vehicle on a busy road. (Inami et al, 2016;Salvia et al, 2016, Desapriya et al, 2014Sun, Xia, Falkmer, & Lee, 2016). Various professions place strong focus on fast response times, and therefore reaction time testing is a key component in assessments for pilots (Truszczynski, Lewkowicz, Wojtkowiak, & Biernacki, 2014) and cosmonauts (Bock, Weigelt, & Bloomberg, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, levocetirizine 5 mg does not affect cognitive functions and car-driving performance . Our recent study also showed that levocetirizine did not impair car-driving performance in young Japanese adults (Inami et al, 2016). A brain histamine H 1 R occupancy (H 1 RO) measure has been added as an objective measure to the Consensus Group on New-Generation Antihistamines (CONGA) (Holgate et al, 2003).…”
mentioning
confidence: 99%